2000
DOI: 10.1287/isre.11.1.83.11784
|View full text |Cite
|
Sign up to set email alerts
|

Productivity of Information Systems in the Healthcare Industry

Abstract: This research paper analyzes the impact of information technology (IT)in a healthcare setting using a longitudinal sample of hospital data from 1976 to 1994. We classify production inputs into labor and capital categories. Capital is classified into three components—medical IT capital, medical capital, and IT capital—and labor is classified into two components, medical labor and IT labor. Results provide evidence that IT contributes positively to the production of services in the healthcare industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
109
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(110 citation statements)
references
References 9 publications
0
109
0
1
Order By: Relevance
“…Although a few studies (Ko & Bryson, 2002;Ko & Osei-Bryson, 2004;Lin & Shao, 2006b) do not find any evidence of a positive correlation, the opposite results are reported by Aral et al (2007), Brynjolfsson & Hitt (1996), Brynjolfsson & Hitt (2000), Kelley (1994), Lin & Shao (2006a), Neirotti & Paolucci (2007), Menon et al (2000), Shin (1997), Stiroh (2002), andSwierczek &Shrestha (2003). In their literature reviews, Devaraj & Kohli (2000) and Dedrick et al (2003) find an overall positive effect on productivity reported in the literature.…”
Section: Impact On Productivitymentioning
confidence: 95%
See 1 more Smart Citation
“…Although a few studies (Ko & Bryson, 2002;Ko & Osei-Bryson, 2004;Lin & Shao, 2006b) do not find any evidence of a positive correlation, the opposite results are reported by Aral et al (2007), Brynjolfsson & Hitt (1996), Brynjolfsson & Hitt (2000), Kelley (1994), Lin & Shao (2006a), Neirotti & Paolucci (2007), Menon et al (2000), Shin (1997), Stiroh (2002), andSwierczek &Shrestha (2003). In their literature reviews, Devaraj & Kohli (2000) and Dedrick et al (2003) find an overall positive effect on productivity reported in the literature.…”
Section: Impact On Productivitymentioning
confidence: 95%
“…Brynjolfsson & Yang, 1996, Baily, 1986Jorgenson & Stiroh, 1995, Roach, 1987, Berndt & Morrison, 1995, Roach, 1991, Loveman, 1994 More recent studies draw a more positive picture of the impact on productivity: productivity paradox has been resolved at firm level; major impact of IS investments on national productivity and economic growth. Aral et al, 2007, Brynjolfsson & Hitt, 1996, Brynjolfsson & Hitt, 2000, Kelley, 1994, Lin & Shao, 2006a, Neirotti & Paolucci, 2007, Menon et al, 2000, Shin, 1997, Stiroh, 2002, Swierczek & Shrestha, 2003, Devaraj & Kohli, 2000, Dedrick et al, 2003, Jorgensen, 2001, Jorgenson & Stiroh, 2000, Oliner & Sichel, 2000 Impact on market performance…”
Section: Impact On Productivitymentioning
confidence: 99%
“…"IT systems are systems that store and provide information about patients, such as the number of patients and the results from an x-ray scan," as has been said by Menon, et al (14) They also state, "The use of IT capital has positive influence on the production of output and thus the efficiency of the planning." The more advanced the IT facilities of a hospital are, the better available the information about the patients and kinds of patients become for the entire hospital, and therefore the better the overview of knowing which patients are where and what treatment have they received and need to receive.…”
Section: Literature and Discussionmentioning
confidence: 99%
“…However, with IS becoming a larger share of total capital investment (Dedrick et al 2003, p. 19), more recent studies find a major impact of IS investments on productivity and economic growth in developed countries (Jorgenson and Stiroh 2000;Oliner and Sichel 2000;Jorgenson 2001). At firm level, the picture seems to be less clear: While some studies (Ko and Bryson 2002;Ko and OseiBryson 2004;Lin and Shao 2006b) do not find any evidence of a positive correlation or suggest a microeconomic explanation (Stickel 1995), opposite results are reported by Hitt (1996, 2000), Kelley (1994), Lin and Shao (2006a), Neirotti and Paolucci (2007), Menon et al (2000), Stiroh (2002), and Swierczek and Shrestna (2003). This leads to the definition of "Research field 2: Productivity".…”
Section: Performance Measurementioning
confidence: 94%